2016
DOI: 10.1155/2016/1517968
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Interlimb Arm and Leg Connections for Walking Rehabilitation: A Training Intervention in Stroke

Abstract: Rhythmic arm and leg (A&L) movements share common elements of neural control. The extent to which A&L cycling training can lead to training adaptations which transfer to improved walking function remains untested. The purpose of this study was to test the efficacy of A&L cycling training as a modality to improve locomotor function after stroke. Nineteen chronic stroke (>six months) participants were recruited and performed 30 minutes of A&L cycling training three times a week for five weeks. Changes in walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 84 publications
7
41
0
Order By: Relevance
“…The focus of future research should be to determine exactly how these changes in reflex excitability are associated with the recovery of motor function. We have recently shown that A & L cycling does indeed transfer to improved walking ability after stroke [39] and the changes in reflex plasticity seen here could be related to this observation. The development of new and targeted therapeutic innovations will further the functional improvements for individuals with neurological disorder.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The focus of future research should be to determine exactly how these changes in reflex excitability are associated with the recovery of motor function. We have recently shown that A & L cycling does indeed transfer to improved walking ability after stroke [39] and the changes in reflex plasticity seen here could be related to this observation. The development of new and targeted therapeutic innovations will further the functional improvements for individuals with neurological disorder.…”
Section: Discussionsupporting
confidence: 65%
“…We hypothesized that A & L cycling training would improve interlimb reflex excitability as assessed by changes in stretch and cutaneous reflex amplitudes. Recently, we have shown that A & L cycling training successfully improves walking after stroke [39], and results from this study may have implications for the mechanistic understanding of plasticity and training transfer following rehabilitative locomotor training in clinical populations.…”
Section: Introductionmentioning
confidence: 87%
“…A multiple baseline repeated measures design was used for this study (Butefisch et al 1995; Kaupp et al 2018; Klarner et al 2016a, b). Multiple baseline measurements were obtained from participants in three baseline sessions over a period of 2 weeks, with a minimum of 24 h between sessions.…”
Section: Methodsmentioning
confidence: 99%
“…A bridging mechanism would be useful to move individuals with severe spasticity to a level of function where they can use other rehabilitation techniques proven to be effective such as arm cycling (Kaupp et al 2018), leg cycling (Sosnoff et al 2009), arm and leg cycling (Klarner et al 2016a, b; Zhou et al 2018) resistance training (Dragert and Zehr 2011; Sun et al 2018) and treadmill walking (Mehrholz et al 2014). Studies investigating repetitive passive movements such as passive leg cycling have been shown to temporarily decrease spasticity (Motl et al 2006, 2007a), therefore passive movement training is one technique which may help ‘bridge’ individuals into other types of rehabilitation by taking advantage of this temporary period of improved function.…”
Section: Introductionmentioning
confidence: 99%
“…Even many years after a stroke, rehabilitation can help. We previously studied how a type of rehabilitation that involved training the arms and legs together on a special bicycle helped people get better at walking after stroke [4,5]. We discovered that this training improved the strength of the arms and legs, the ability to walk, and the nerve connections between the arms and legs.…”
Section: Can Training Help a Person After A Stroke?mentioning
confidence: 99%